2018
DOI: 10.3390/ijms19041141
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Understanding the Molecular Biology of Disease Resistance in Rice

Abstract: Rice is one of the important crops grown worldwide and is considered as an important crop for global food security. Rice is being affected by various fungal, bacterial and viral diseases resulting in huge yield losses every year. Deployment of resistance genes in various crops is one of the important methods of disease management. However, identification, cloning and characterization of disease resistance genes is a very tedious effort. To increase the life span of resistant cultivars, it is important to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 375 publications
(253 reference statements)
0
24
0
Order By: Relevance
“…Disease resistance alleles from crop gene pool can be introgressed into high yielding varieties to further improve their capacity to overcome the challenges of pathogen attack [34]. Rice blast disease can be effectively managed by the utilisation of R gene which can be taken from the resistant varieties to develop high yielding varieties either by breeding or in raising transgenics [35]. The copy number variation, nucleotide diversity, substitutions at the R genes loci are sources of allelic variation [17,36].…”
Section: Discussionmentioning
confidence: 99%
“…Disease resistance alleles from crop gene pool can be introgressed into high yielding varieties to further improve their capacity to overcome the challenges of pathogen attack [34]. Rice blast disease can be effectively managed by the utilisation of R gene which can be taken from the resistant varieties to develop high yielding varieties either by breeding or in raising transgenics [35]. The copy number variation, nucleotide diversity, substitutions at the R genes loci are sources of allelic variation [17,36].…”
Section: Discussionmentioning
confidence: 99%
“…The plant defense response against biotic stresses can be categorized into pathogen-associated molecular patterns (PAMP)-triggered immunity (PTI) and effector-triggered immunity (ETI) [1]. In both PTI and ETI, the activation of a complex network of signaling cascade pathways leads to the induction of resistance response mediated through pathogenesis-related ( PR ) genes, reactive oxygen species (ROS) and secondary metabolites [2]. The initiation of PR proteins against various biotic stresses has been reported in different plant species [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…As we succeeded in identifying other BSR-resistant cultivars besides 'Nona Bokra', it might be possible to identify other new QTLs that will be useful for gene pyramiding to improve BSR resistance. Although many disease resistance genes have been cloned and characterized in rice (Singh et al 2018), no resistance genes associated with BSR or BGR have yet been identified. The cloning of RBG1 and RBG2 is under way to clarify their genetic mechanisms.…”
Section: Bsmentioning
confidence: 99%